2020
DOI: 10.1093/tas/txaa083
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of zinc and copper sources and phytase on growth performance, mineral digestibility, bone mineral concentrations, oxidative status, and gut morphology in nursery pigs

Abstract: Abstract This study investigated the interactive effects of zinc (Zn) and copper (Cu) sources and phytase on growth performance, oxidative status, mineral digestibility, tissue mineral concentrations, and gut morphology in nursery pigs. A total of 288 weaning barrows [body weight (BW) = 5.71 ± 0.81 kg], blocked by initial BW, were randomly allotted to one of eight dietary treatments, with nine pens per treatment and four pigs per pen. The eight dietary treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 59 publications
3
20
0
Order By: Relevance
“…The current study demonstrated that Zn-Met added in feed improved Zn apparent digestibility. This is in agreement with previous studies, in which organic Zn sources such as Zn-Met, Zn-proteinate and Zn-glycinate had a greater bioavailability as compared to inorganic Zn forms [ 23 , 24 , 25 ]. Moreover, this study found that ZnSO 4 dissolved in drinking water also had higher Zn apparent digestibility in comparison with ZnSO 4 added in feed.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The current study demonstrated that Zn-Met added in feed improved Zn apparent digestibility. This is in agreement with previous studies, in which organic Zn sources such as Zn-Met, Zn-proteinate and Zn-glycinate had a greater bioavailability as compared to inorganic Zn forms [ 23 , 24 , 25 ]. Moreover, this study found that ZnSO 4 dissolved in drinking water also had higher Zn apparent digestibility in comparison with ZnSO 4 added in feed.…”
Section: Discussionsupporting
confidence: 93%
“…Zn-Met, organic metal chelates composed of Zn chelated with Met in coordinate covalent bonds, chelate is stable in the small intestine, may minimize the formation of Zn-phytate complex and allow more Zn to be absorbed by the epithelial cells in the small intestine [ 22 ]. In contrast, inorganic form, ZnSO 4 , is easily dissociated in the stomach and intestine, therefore, Zn-phytate complex is formed, rendering a lower absorption of Zn [ 23 ]. The current study demonstrated that Zn-Met added in feed improved Zn apparent digestibility.…”
Section: Discussionmentioning
confidence: 99%
“…Technology advancement has led to the development of numerous forms of organic Cu, which have been shown to be more bioavailable than CuSO 4 [3]. Studies have demonstrated that Cu-proteinate [5] and Cu-MHAC [6,7,9] achieved greater growth performance in nursery pigs than CuSO 4 at the same Cu inclusion levels, which was further supported by the current study that Cu-MHAC achieved greater average daily gain than CuSO 4 in the presence of phytase supplementation at 1500 FTU/kg. The fact that average daily gain in nursery pigs was not different between Cu-MHAC and CuSO 4 without phytase in the present study indicated that the impact of P deficiency might overshadow the beneficial effect of Cu-MHAC or P deficiency may impair the function and utilization of Cu in the body.…”
Section: Discussionsupporting
confidence: 79%
“…An in vitro model has demonstrated that Cu lysine is less inhibitive to phytase compared with CuSO 4 [11]. Our recent data also suggests that Cu-MHAC may enhance phytase efficacy on bone mineralization in nursery pigs when 500 FTU/kg phytase is used, compared with CuSO 4 [9]. However, there is no data on the interaction of copper source and phytase supplementation at high levels on growth performance and mineral digestibility in pigs.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation